The Role of Peroxisome Proliferator-Activated Receptor Gamma and Atherosclerosis: Post-translational Modification and Selective Modulators - Yin, Liqin; Wang, Lihui; Shi, Zunhan; Ji, Xiaohui; Liu, Longhua (Frontiers in Physiology, 2022)
Atherosclerosis is the hallmark of cardiovascular disease(CVD) which is a leading cause of death in type 2 diabetes patients, and glycemic control is not beneficial in reducing the potential risk of CVD. Clinically, it was shown that Thiazolidinediones (TZDs), a class of peroxisome proliferator-activated receptor gamma (PPARγ) agonists, are insulin sensitizers with reducing risk of CVD, while the potential adverse effects, such as weight gain, fluid retention, bone loss and cardiovascular risk, restricts its use in diabetic treatment. PPARγ, a ligand-activated nuclear receptor, has shown to play a crucial role in anti-atherosclerosis by promoting cholesterol efflux, repressing monocytes infiltrating into the vascular intima under endothelial layer, their transformation into macrophages, and inhibiting vascular smooth muscle cells proliferation as well as migration. The selective activation of subsets of PPARγ targets, such as through PPARγ post-translational modification, is thought to improve the safety profile of PPARγ agonists. Here, this review focuses on the significance of PPARγ activity regulation (selective activation and post-translational modification) in the occurrence, development and treatment of atherosclerosis, and further clarifies the value of PPARγ as a safe therapeutic target for anti-atherosclerosis especially in diabetic treatment.